SORPTION-ATOMIC ABSORPTION DETERMINATION OF METAL ULTRATRACES IN MARINE AND RIVER PARTICULATE MATTER - Oreshkin V.N.; Tsizin G.I. (My University, 2003)
Summarizing the data we may note that the proposed sorption-AA method for determining metal traces in small amounts of marine and river particulate matter supplements the existing complex of analytical methods applied for this purpose. It can provide new analytical information on the abundance of toxic heavy metals, particularly in poorly studied oceanic particulate matter. It is expedient to analyze the collection of unique samples obtained in expeditions in various regions of the World Ocean.